Plan de negocios para la creación de una empresa productora y comercializadora de queso fresco y maduro en el cantón La Maná año 2013 - Moran Macías, Luis Alfredo (2014)
This research aims to determine the feasibility of a business plan for the creation of a producer and distributor of fresh and ripe cheese company located in La Maná Canton, initially with cantonal coverage for future expansion with zonal coverage. The results of this research are summarized in a diagnosis applied to the environment of the project, the favorable market conditions and obtaining the raw material were determined, on the other hand the opportunities are significant and future risks can be controlled....